Pengaruh Manajemen Laba Dan Profitabilitas Perusahaan Terhadap Nilai Perusahaan Sebelum Dan Selama Pandemi Covid-19 - Tarisa Arnelia Syabilla; Ki Agus Andi (CV. Aksara Global, 2023)
This study aims to test empirically whether there are differences in earnings management and company profitability before and during the COVID-19 pandemic in Indonesia. In this study the population used comes from the financial report data of companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The method used was purposive sampling in order to obtain a sample of 30 sample data. The type of data used is secondary data. Data analysis used the Independent Sample T-Test different test with SPSS 25 software. The results of this study indicate that there is not significant differences in real earnings management before and during the COVID-19 pandemic in Indonesia carried out by pharmaceutical sector companies listed on the IDX for the 2019-2021 period. As well as there are significant differences in profitability in pharmaceutical sector companies before and during the COVID-19 pandemic in Indonesia.